Low-cost Free-standing ferroelectric polymer films with high polarization produced via pressing-and-folding - Nan Meng; Xintong Ren; Jiyue Wu; Emiliano Bilotti; Michael J. Reece; Haixue Yan (Journal of Materiomics, 2022)
Ferroelectric polymer poly (vinylidene fluoride) (PVDF) shows excellent electro-activity and is promising for flexible electronic devices. However, the processing of PVDF into the favourable ferroelectric structure (β-phase) presents difficulties, while its copolymer with trifluoroethylene (PVDF-TrFE) can directly crystallize into β-phase, but shows limited thermal stability and high-cost processing. As a result, an easily implementable method, pressing-and-folding (P&F), was used to produce highly compatible blended films of PVDF and PVDF-TrFE without using any hazardous solvent or complex polymer processing equipment. Hot-pressed PVDF (molecular weight: 530 kg/mol) and PVDF-TrFE (molar ratio: 51/49) films were firstly stacked before undergoing P&F treatment. Compared to extrusion-blended films before and after P&F, the P&F stacked films showed isotropic crystalline structure of β-phase, as confirmed using X-ray diffraction and infrared spectroscopy. The ferroelectric remnant polarization of the P&F stacked films is 0.068 C/m2, surpassing pure PVDF-TrFE (0.062 C/m2) and the simulated value of remnant polarization of pure PVDF (～0.065 C/m2). The above findings promise to provide inspirations for new processing strategy on PVDF-based functional polymers.